Endometriosis, difficulties in early diagnosis and female infertility: A review (Research, Society and Development, 2021)
Endometriosis is a pathology that affects thousands of women worldwide, this is due to the presence of extrauterine endometrial tissue, which responds to hormonal stimulation and can cause an inflammatory reaction resulting in symptoms such as severe chronic pelvic pain and infertility. In Brazil, about 7 million women suffer from the disease, whose diagnosis, medical records and research are highly deficient, making it difficult for patients to recover. Thus, this study aimed to investigate the difficulties in the early diagnosis of endometriosis and its relation with female infertility through a narrative review. Bibliographic searches were carried out in the following databases: SciELO, PubMed/MEDLINE and BVS, as these are databases that concentrate publications of excellence focused on the health area. The selection of studies published in the databases was understood between the years 2001 to 2021, using the descriptors recognized by the DECs: "Endometriosis", "Early Diagnosis", "Infertility Female" and "Treatmet Alternatives". Thus, we obtained results from studies that address aspects involved in the difficulty of obtaining an early diagnosis of endometriosis, in addition to the available treatments. In which we show that endometriosis is still a disease of uncertain etiopathogenesis, and that this uncertainty contributes to the difficulty of diagnosing the disease, in which one of the biggest factors that hinder the early diagnosis of endometriosis is the lack of information.